Estrogen protects against the synergistic toxicity by HIV proteins, methamphetamine and cocaine - Turchan, Jadwiga (BioMed Central, 2001)
BACKGROUND: Human immunodeficiency virus (HIV) infection continues to increase at alarming rates in drug abusers, especially in women. Drugs of abuse can cause long-lasting damage to the brain and HIV infection frequently leads to a dementing illness.To determine how these drugs interact with HIV to cause CNS damage, we used an in vitro human neuronal culture characterized for the presence of dopaminergic receptors, transporters and estrogen receptors. We determined the combined effects of dopaminergic drugs, methamphetamine, or cocaine with neurotoxic HIV proteins, gp120 and Tat. RESULTS: Acute exposure to these substances resulted in synergistic neurotoxic responses as measured by changes in mitochondrial membrane potential and neuronal cell death. Neurotoxicity occurred in a sub-population of neurons. Importantly, the presence of 17beta-estradiol prevented these synergistic neurotoxicities and the neuroprotective effects were partly mediated by estrogen receptors. CONCLUSION: Our observations suggest that methamphetamine and cocaine may affect the course of HIV dementia, and additionally suggest that estrogens modify the HIV-drug interactions.